2021
DOI: 10.1103/physrevb.104.235303
|View full text |Cite
|
Sign up to set email alerts
|

Electrical control of the g tensor of the first hole in a silicon MOS quantum dot

Abstract: Single holes confined in semiconductor quantum dots are a promising platform for spin-qubit technology, due to the electrical tunability of the g factor of holes. However, the underlying mechanisms that enable electric spin control remain unclear due to the complexity of hole-spin states. Here, we study the underlying hole-spin physics of the first hole in a silicon planar metal-oxide-semiconductor (MOS) quantum dot. We show that nonuniform electrode-induced strain produces nanometer-scale variations in the he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…Note that numerous experiments have shown that g tensors of electrons confined in semiconductors can be tuned in situ by electric fields [31,[34][35][36][37]. Therefore, we regard the spinorbit-affected parameters, that is, the matrix elements of the g tensors, the exchange strength J, and the exchange rotation R, as tunable parameters.…”
Section: Setup and Background: Spin-orbit-coupled Two-spin Systemmentioning
confidence: 99%
“…Note that numerous experiments have shown that g tensors of electrons confined in semiconductors can be tuned in situ by electric fields [31,[34][35][36][37]. Therefore, we regard the spinorbit-affected parameters, that is, the matrix elements of the g tensors, the exchange strength J, and the exchange rotation R, as tunable parameters.…”
Section: Setup and Background: Spin-orbit-coupled Two-spin Systemmentioning
confidence: 99%
“…Therefore, the shear strains εyz, εxz, and εxy drive rotations of the principal magnetic axes around x, y and z respectively. We can recover the experimental rotations assuming small εyz 0.035% and εxz 0.080%, which highlights the sensitivity of such quantum devices to residual strains 24,30,40 . Note that the possible rotation of the principal axes around z can not be resolved since the g-factors have not been measured in the xy plane (but may improve the overall agreement between theory and experiment, in particular for LSESG1); The detailed assessment of strains in such complex nanostructures is, however, difficult (in particular in the nitrides), and goes beyond the scope of this work.…”
Section: B Discussionmentioning
confidence: 55%
“…The fact that Z is not aligned along the channel implies a loss of the xy quasi-symmetry plane of gate G2 24 , and the existence of additional heavy-hole/light-hole mixing mechanisms. The most likely scenario is that QD2 is slightly displaced towards G3 (as suggested above), and experiences small process and cool-down strains 24,30 . In particular, shear strains control the phase of the heavy-hole/light-hole mixing matrix elements.…”
Section: B Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…All-electrical control of spin qubits via the spinorbit interaction can be used to achieve faster and more scalable control, however, the intrinsic spin-orbit coupling of electron spins are too weak to induce high-fidelity coherent rotations 5 . In contrast, hole spins are subject to stronger spin-orbit fields, enabling fast two-axis control of the qubit albeit with the drawback of sub-microsecond coherence times [6][7][8][9][10] .…”
mentioning
confidence: 99%